A rapid live-cell ELISA for characterizing antibodies against cell surface antigens of Chlamydomonas reinhardtii and its use in isolating algae from natural environments with related cell wall components - Jiang, Wenzhi; Cossey, Sarah; Rosenberg, Julian N.; Oyler, George A.; Olson, Bradley J. (My University, 2015)
Background: Cell walls are essential for most bacteria, archaea, fungi, algae and land plants to provide shape, structural integrity and protection from numerous biotic and abiotic environmental factors. In the case of eukaryotic algae, relatively little is known of the composition, structure or mechanisms of assembly of cell walls in individual species or between species and how these differences enable algae to inhabit a great diversity of environments. In this paper we describe the use of camelid antibody fragments (VHHs) and a streamlined ELISA assay as powerful new tools for obtaining mono-specific reagents for detecting individual algal cell wall components and for isolating algae that share a particular cell surface component. Results: To develop new microalgal bioprospecting tools to aid in the search of environmental samples for algae that share similar cell wall and cell surface components, we have produced single-chain camelid antibodies raised against cell surface components of the single-cell alga, Chlamydomonas reinhardtii. We have cloned the variable-region domains (V[subscript H]Hs) from the camelid heavy-chain-only antibodies and overproduced tagged versions of these monoclonal-like antibodies in E. coli. Using these V[subscript H]Hs, we have developed an accurate, facile, low cost ELISA that uses live cells as a source of antigens in their native conformation and that requires less than 90 minutes to perform. This ELISA technique was demonstrated to be as accurate as standard ELISAs that employ proteins from cell lysates and that generally require >24 hours to complete. Among the cloned V[subscript H]Hs, V[subscript H]H B11, exhibited the highest affinity (EC[subscript 50] < 1 nM) for the C. reinhardtii cell surface. The live-cell ELISA procedure was employed to detect algae sharing cell surface components with C. reinhardtii in water samples from natural environments. In addition, mCherry-tagged V[subscript H]H B11 was used along with fluorescence activated cell sorting (FACS) to select individual axenic isolates of presumed wild relatives of C. reinhardtii and other Chlorphyceae from the same environmental samples. Conclusions: Camelid antibody V[subscript H]H domains provide a highly specific tool for detection of individual cell wall components of algae and for allowing the selection of algae that share a particular cell surface molecule from diverse ecosystems.
Keywords: Live-cell ELISA; Camelid antibodies; Algae; Cell walls; Cell wall conservation; Nanobodies